Case report: Gross persistent rectal prolapse. A case treated without mesh using deep retrorectal dissection/suturing - Miyano, Go; Yamada, Shunsuke; Murakami, Hiroshi; Lane, Geoffrey J.; Yamataka, Atsuyuki (Frontiers in Pediatrics, 2022)
A previously well 15-year-old male presented with a history of gross rectal prolapse (GRP) involving full-thickness rectal prolapse of increasing severity and incidence over 6 months that occurred with every bowel motion, varying from 10 to 40 cm. He denied constipation and passed a soft motion once daily, adeptly reducing his prolapsed rectum after each motion. This case illustrates technical challenges and planning for surgical intervention for optimal treatment in keeping with an FDA alert issued April, 2019 banning surgical mesh for pelvic organ prolapse. Preoperative fluoroscopic defecography confirmed rectal prolapse beginning with eversion of the anal verge identified on inspection. For surgery, general anesthesia was induced, he was placed in a Trendelenburg position, and four ports were inserted. The peritoneum was incised and blunt dissection used to expose the levator ani complex (LAC) taking care to prevent lateral nerve injury and preserve regional vascularity. Seven polypropylene sutures were used to fix the seromuscular posterior wall of the rectum to the median raphe of the LAC, the presacral fascia, and the periosteum of the sacral promontory. Operative time was 170 min. Postoperative recovery and progress were unremarkable. Currently, 5 years postoperatively, defecation is regular without recurrence of prolapse. For prolapse involving protrusion of the upper rectum without eversion of the anal verge, rectal fixation to the sacral promontory without further dissection beyond the peritoneal reflection is adequate, but when extensive prolapse is associated with eversion of the anal verge, more extensive blunt dissection from the peritoneal reflection to the LAC with multiple rectopexy sutures is valid for reducing risks for recurrence and eliminating mesh-related complications.